2017
DOI: 10.1111/cch.12494
|View full text |Cite
|
Sign up to set email alerts
|

Peer support for families of children with complex needs: Development and dissemination of a best practice toolkit

Abstract: The toolkit format was valuable to synthesize and share best practices in peer support. Strengths of the work include the integrated approach used to develop the toolkit and the inclusion of both the published research literature and experiential evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
(30 reference statements)
0
9
0
1
Order By: Relevance
“…Specifically, social support from parents or peers, also referred as “peer support networks,” provides mutual support between parents who share similar experiences ( 14 ). The benefits of peer support networks for families have been previously identified in caregiving populations as enabling members to share their feelings, providing a sense of belonging to the community, and enlarging their social networks to include other families who can lend a hand during difficult times ( 15 ). Despite the acknowledged importance of the value of peer support networks for many complex conditions, we did not find studies that have reviewed in depth, the literature solely focused on peer support networks for families of children with NDID.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, social support from parents or peers, also referred as “peer support networks,” provides mutual support between parents who share similar experiences ( 14 ). The benefits of peer support networks for families have been previously identified in caregiving populations as enabling members to share their feelings, providing a sense of belonging to the community, and enlarging their social networks to include other families who can lend a hand during difficult times ( 15 ). Despite the acknowledged importance of the value of peer support networks for many complex conditions, we did not find studies that have reviewed in depth, the literature solely focused on peer support networks for families of children with NDID.…”
Section: Introductionmentioning
confidence: 99%
“…2 There is growing evidence of the benefits of peer support programs for families of children with complex medical needs and disabling conditions. [3][4][5][6][7] Various peer support interventions are available today, but high-quality evidence about the potential benefits and the best practice model of peer support is lacking. 3 The current Cochrane Review 1 attempts to identify evidence of the effects of peer support interventions compared with usual care or alternate interventions for parents and family caregivers of disabled children with complex medical needs in different settings.…”
Section: Backgrou N Dmentioning
confidence: 99%
“…Parents and family caregivers of children with complex needs who participate in daily caregiving activities often experience lower levels of psychological, emotional, and social well‐being compared to parents and family caregivers of typically developing children 2 . There is growing evidence of the benefits of peer support programs for families of children with complex medical needs and disabling conditions 3–7 . Various peer support interventions are available today, but high‐quality evidence about the potential benefits and the best practice model of peer support is lacking 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Leading from Bowlby's ( 45 ) work on attachment theory, some interventions with foster parents focus on developing a secure relationship between foster parents and the children in their care. These studies have found promising decreases in behavioral challenges among children who have experienced maltreatment ( 46 48 ). This lends evidence for the effectiveness of relational approaches to ameliorating the impacts of childhood maltreatment by improving the relational health of these children.…”
Section: Literature Reviewmentioning
confidence: 99%